2008
DOI: 10.7150/ijms.5.189
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Alters Gene Expression in the MCF7 Breast Cancer Cell Line: Evidence for an Anti-Estrogen Effect of Iodine

Abstract: The protective effects of iodine on breast cancer have been postulated from epidemiologic evidence and described in animal models. The molecular mechanisms responsible have not been identified but laboratory evidence suggests that iodine may inhibit cancer promotion through modulation of the estrogen pathway. To elucidate the role of iodine in breast cancer, the effect of Lugol's iodine solution (5% I2, 10% KI) on gene expression was analyzed in the estrogen responsive MCF-7 breast cancer cell line. Microarray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 46 publications
(47 reference statements)
2
49
0
1
Order By: Relevance
“…Some of the primary risk factors for female breast cancer include age (2), lack of childbearing or breastfeeding (3), high hormone levels (e.g., estrogen) (4), and ethnicity (5). However, diet is another important factor that contributes to the development of breast cancer (6)(7)(8). The impact of diet on the incidence of breast cancer is indicated by geographic differences in the occurrence of the disease (9), and by the many dietary components experimentally proven to act as antibreast cancer agents.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the primary risk factors for female breast cancer include age (2), lack of childbearing or breastfeeding (3), high hormone levels (e.g., estrogen) (4), and ethnicity (5). However, diet is another important factor that contributes to the development of breast cancer (6)(7)(8). The impact of diet on the incidence of breast cancer is indicated by geographic differences in the occurrence of the disease (9), and by the many dietary components experimentally proven to act as antibreast cancer agents.…”
Section: Introductionmentioning
confidence: 99%
“…Iodine may also be affecting the binding of estrogen receptors to the steroid-binding element. Using breast cancer cells (MCF-7 cells), Stoddard and colleagues demonstrated that Lugol's solution (5% iodine/10% iodide) affected 43 genes involved cell cycle growth, proliferation, and differentiation [19]. Many of the 43 genes are those up regulated by estrogens, implying that the Lugol's solution interfered with this action and had a net "anti-estrogenic" effect on gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-documented that molecular iodine (I 2 ) has a potent antitumor effect on mammary cancer in rats via regulating the cell oxidative environment (25). A gene array study showed that PVP-I inhibits breast cancer (MCF-7) through modulation of the estrogen pathway (26). Moreover, Shrivastava et al (27) have showed that iodine induced human breast cancer cell (MCF-7) death through activating a caspase-independent and mitochondria-mediated apoptotic pathway.…”
Section: Discussionmentioning
confidence: 99%